Ficus carica and bone health: a systematic review - Ruszymah Hj. Idrus,; Nur Qisya Afifah Veronica Sainik,; Ayu Suraya Ansari,; Mohamed S. Zulfarina,; Rabiatul Adawiyah Razali,; Abid Nordin,; Aminuddin Saim,; Isa Naina-Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ficus carica, a native plant to the Middle East and Western Asia, is of high value in folk medicine. The therapeutic potential of Ficus carica has led to the extensive studies in recent years, focusing on evaluating and validating its pharmacological effect. The present systematic review summarizes the effectiveness of Ficus carica on promoting bone health focusing on osteoporosis and rheumatoid arthritis via mineral contents and RANKL pathway. The search was done with Medline via Ebscohost, Scopus and Google Scholar databases to obtain relevant articles published between 1946 and December 2016. The main inclusion criteria were research articles published in English that reported effect of Ficus carica on bone health. The literature search returned 716 potentially relevant articles, whereby 5 met the inclusion criteria. This systematic review concludes Ficus carica plays an important role in the promotion of bone health and can be a potential pharmaceutical product in the future.